Mediastinal Lymphohemangioma (Case Report): A (Report of a) Rare Case with Difficult Diagnosis - ramadhan, fitratul; Pratiwiw, Suryanti; Isharanto, Artono; Erawati, Dini; Yudhanto, Hendy (Universitaas Brawijaya, 2022)
Mediastinal lymphohemangioma is a very rare, benign, congenital malformation. Mediastinal lymphohemangioma originates from local proliferation of lymphatic vessels. This disorder is accountable for 4.5% among all mediastinal tumors. Most lymphohemangiomas are found in the neck and axillary region among children, whereas only 1% are found in the mediastinum and tend to occur in individuals aged over 20 years old. A proper understanding is needed to be able to make a diagnosis and perform effective management of mediastinal lymphohemangiomaIn this case report, a woman with a diagnosis of mediastinal lymphohemangioma, established through a multidisciplinary approach covering the fields of pulmonology, thoracic and cardiovascular surgery, radiology, and anatomical pathology.Keywords: Mediastinal Lymphohemangioma, Core Biopsy, Thoracotomy